Evo & Lusi: A Novel to Increase Motivation to Learn Evolution - Setiyo Prajoko; Ika Sukmawati; Tegar Satya Prahara (Universitas Lampung, 2023)
This study aims to determine the feasibility of evolution learning novels as an alternative learning resource in high school biology learning and to determine the effectiveness of evolution learning novels in increasing learning motivation in students. The research method used is Research and Development (RD). The type of research and development used is the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). The implementation stage is carried out with a pre-experimental design type one-group pretest and post design. The validation results that have been carried out, the product developed has an average validation percentage of 82.5%, which is very valid. The percentage of validation is obtained from the validation results by learning novel development experts and evolutionary material experts, but with various revisions that need to be made, the majority of which lie in writing errors and laying the concept of evolution. The products produced increased student learning motivation when tested on a limited basis at SMA N 1 Bandar Batang Regency. The initial motivation level of SMA N 1 Bandar Batang Regency students is included in the excellent category with a percentage of 59.17%. After being given a novel to read, the student motivation level increase to 79.86% or in high criteria. The results obtained, the product produced as an evolution learning novel is included in the category of feasible and quite effectiveÂ DOI: http://dx.doi.org/10.23960/jbt.v11.i1.26992